Fiscal Policy and Occupational Employment Dynamics - Christian Bredemeier; Falko Juessen; Roland Winkler (Institute of Labor Economics (IZA), 2017)
We document substantial heterogeneity in occupational employment dynamics in response to government spending shocks. Employment rises most strongly in service, sales, and office ("pink-collar") occupations. By contrast, employment in blue-collar occupations is hardly affected by fiscal stimulus which is striking in light of its strong exposure to the cycle and its long-run decline due to technical change and globalization. We provide evidence that occupation-specific changes in labor demand are key to understand these findings and develop a business-cycle model that explains the heterogeneous occupational employment dynamics as a consequence of differences in the short-run substitutability between labor and capital services across occupations.
Keywords: E62; E24; J21; J23; 330; fiscal policy; composition of employment; occupations; industries; heterogeneity